PELI3-Mediating Epithelial-Mesenchymal Transition Correlates with Radiation Sensitivity in Non-Small Cell Lung Cancer - Li, Fannian; Li, Xiaoning; Li, Haitao; Li, Shuai; Liu, Yanchao; Bai, Xianhua; Qi, Tianjie; Zhao, Xiumin; He, Yuzheng (Current Medicinal Chemistry, 2026)
<span class=
Keywords: non-small cell lung cancer